Sensory attributes and functional properties of maillard reaction products derived from the crassosotrea gigas (Ostrea rivularis gould) enzymatic hydrolysate and xylose system - Fuli Wen; Chao Zeng; Yang Yang; Tao Xu; Hongmei Wang; SongTao Wang (Heliyon, 2023)
To improve the flavor of Ostrea rivularis Gould, enzymatic hydrolysis was conducted and xylose-OEH Maillard reaction products were prepared. Then, their physicochemical properties and metabolites were determined by UHPLC-MS-MS, and volatile compounds were determined by GC-MS to investigate the changes. The results showed that His, Gln, Lys, Asp, and Cys were the major amino acids consumed. After being heated at 120 °C for up to 150 min, the DPPH (2,2-Diphenyl-1-picrylhydrazyl) was 85.32 ± 1.35% and the reducing capacity was 1.28 ± 0.12. Both were the highest in the groups. Additionally, 45 volatile compounds, including 2-ethyl-5-methyl-pyrazine and 2-ethyl-3,5-dimethyl-pyrazine, and 678 compounds were identified. We also found that 18 metabolites with significant differences (VIP ≥2) were differential metabolites, which involved lipid oxides and amino acid derivatives. The content of lipids favored the regulation of Maillard products and affected the lower threshold of the flavor of aldehydes, which contributed to the flavor and antioxidant activity. These results suggested the potential of xylose-OEH MRPs as a natural antioxidant for further processing oysters.